2017
DOI: 10.1002/tea.21421
|View full text |Cite
|
Sign up to set email alerts
|

Young children's near and far transfer of the basic theory of natural selection: An analogical storybook intervention

Abstract: Misconceptions about adaptation by natural selection are widespread among adults and likely stem, in part, from cognitive biases and intuitive theories observable in early childhood. Current educational guidelines that recommend delaying comprehensive instruction on the topic of adaptation until adolescence, therefore, raise concerns because children's scientifically inaccurate theories about species may be left unchallenged for many years, allowing them to entrench and become difficult to overcome. In consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 74 publications
5
59
0
1
Order By: Relevance
“…Previous work (Emmons et al 2017;Emmons et al 2016;Kelemen et al 2014) has shown that children as young as 5 years of age are able to form a basic understanding of evolution after listening to the storybook How the piloses evolved skinny noses (Kelemen and The Child Cognition Lab 2017). However, these studies have been conducted in highly scripted settings, where children have been read to and interviewed one-on-one.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work (Emmons et al 2017;Emmons et al 2016;Kelemen et al 2014) has shown that children as young as 5 years of age are able to form a basic understanding of evolution after listening to the storybook How the piloses evolved skinny noses (Kelemen and The Child Cognition Lab 2017). However, these studies have been conducted in highly scripted settings, where children have been read to and interviewed one-on-one.…”
Section: Discussionmentioning
confidence: 99%
“…As described, there is a large body of empirical work (e.g. Emmons et al 2016;Emmons et al 2017;Kelemen et al 2014) that aims to use the book How the piloses evolved skinny noses (Kelemen and The Child Cognition Lab, 2017) as a scripted invention for learning evolution. This paper intend to shed light on the complex meaning-making processes occurring during interactive read aloud of science themes books.…”
Section: Interactive Read Aloud and Meaning Making In Sciencementioning
confidence: 99%
See 3 more Smart Citations